Synthesis of Schiff Bases from 2-Amino-4, 6-diphenyl Pyrimidines and 2-Amino-4,6-Diphenyl-5, 6-Dihydro Pyrimidines and Evaluation of Antimicrobial and Anticancer Activities - Anjali Milind Rahtgaonkar, Mrs.; Ghiya, B.J. (Asian Journal of Chemistry, 2010)
Schiff bases were prepared by the condensation of 2-arnino-diarylpyrimidines and 2-arnino-diaryl-dihydro pyrimidines with substituted benzaldehydesin ethanol with 2-3 drops of H2SO4 as a condensing agent.The synthesised pyrimidines and their Schiff bases were futher studied forthe evaluation of antimicrobial and anticancer activities.